Dynamics and Hydrocarbon Degrading Potential of Microorganisms Associated With Long-Term Polluted Site in South-South Nigeria - Nkanang, A.; Umana, S.; Eduok, S. (Journal of Science, Technology and Innovation Research, 2026)
The dynamics and hydrocarbon degrading potential of microorganisms associated with long-term polluted soils near automobile workshops in Uyo metropolis was evaluated using standard microbiological techniques. The result indicates total heterotrophic and hydrocarbon utilizing bacterial counts of 5.74 and 4.92 Log₁₀CFU/g, whereas heterotrophic mould and yeast counts were 4.06 and 5.19 log10CFU/g respectively. Heterotrophic microbial abundance was higher than the hydrocarbon degraders and the difference was significant at p = 0.05. Hydrocarbon degrading bacteria identified were members of genera Pseudomonas, Bacillus, Micrococcus, Proteus, and fungal species Yarrowia lipolytica, Candida tropicalis, and Mucor hiemalis. Micrococcus, Pseudomonas, Candida tropicalis and Candida pseudotropicalis exhibited high degradative potential with growth diameter of 15,10, 10 and 9 mm respectively. The respiration rate in the control soil was 0.02 mg CO₂ g d⁻¹ compared to 0.24 mgCO₂ g d⁻¹ in the polluted soil. The total petroleum hydrocarbon concentration of 1.3 mg/kg in the polluted soil was 6.5 times higher than 0.2 mg/kg in the control. The heavy metal concentration which ranged from 0.1 to 3.26 mg/kg in the order Zn>V > Pb > Fe > Ni > Co were within the WHO permissible limits and caution should be taken to avoid accumulation and biomagnification in the environment. Overall, hydrocarbon exposed microorganisms, Pseudomonas sp. and Candida tropicalis exhibited competitive advantage in their degrading potentials and are good candidates to be harnessed in remediation of contaminated site.